Soy deactivated in semi feedlot diets for heifers 1/2 angus-Nellore - Marques, Orlando Filipe Costa; Oliveira, Euclides Reuter de; Gandra, Jefferson Rodrigues; Fernandes, Alexandre Rodrigo Mendes; Gabriel, Andréa Maria de Araújo; Silva, Janaina Tayna; Neves, Nathálie Ferreira; Valentim, Jean Kaique (Acta Scientiarum. Animal Sciences, 2024)
This research evaluated the effects of diets containing or not containing deactivated soybean sums on productive performance, carcass attributes, carcass ultrasound, and feed cost in confined heifers with 1/2 Nellore-Angus blood. We used blood from 60 1/2 Nellore-Angus heifers aged 2 or 25 years with a body weight of 404.62 kg. A completely randomized design was used, in which the animals were divided into 2 experimental groups: Cont (concentrated for semi feedlot without added deactivated soybean) and Bocchi (concentrated for semi feedlot with the addition of deactivated soybeans). There was no significant difference in the final weight between the experimental groups or for the consumption of concentrate in the evaluation periods. However, heifers supplemented with deactivated soybean in the diet showed greater daily weight gain than did those in the Cont group, as well as greater carcass weight, arrobas gain, and carcass yield. Bocchi concentrate was less expensive than Cont (U 7.26 ton-1). The addition of deactivated soybean for finishing cattle is indicated because it provided the animals with higher energy intake and positively influenced the productive performance as a final weight gain greater than that of the feed without adding the deactivated soybean in addition to lower production cost.